APPLYING THE BORG'S RATINGS OF PERCEIVED EXERTION SCALE TO ASSESS MOTOR DEVELOPMENT IN ONLINE UNIVERSITY LEARNING - P. Angelova; D. Ignatova (Trakia Journal of Sciences)
Physical education and sports lecturers should evaluate the impact of physical exercises proposed for implementation in the home environment. The use of self-report scales for the degree of physical exertion is a valuable tool for objectivity and tracking the physical effort exerted by students. The Borg Scale of Perceived Exertion(RPE)that subjects self-report exercise intensity during exercise. This paper aims to analyze the available literature regarding the application and validity of the scale and to determine whether the Borg of Perceived Exertion Scale can be applied during distance education in physical education and sports at the university. This narrative review combines theoretical analysis and reflective insights to gather information about the suitability of the Borg scale for use in distance learning students in physical education and sports. Results and discussion: During the search for innovative methods of work in the discipline of Physical Education and Sport, no data on the use of the Borg Scale in students were found. According to the available scientific studies, the Borg Scale is a good tool that can be used to plan the intensity of training programs, assess physical exertion, and as a means of controlling recovery from physical fatigue. Conclusion: The use of the scale as a tool for self-assessment by students of the degree of physical exertion will facilitate the optimization of academic and sports programs at the university. In this way, the physical load would correspond more precisely to the individual motor qualities and physical capabilities of the students.